Efektivitas Program Beras Sejahtera (Rastra) Dalam Meningkatkan Kesejahteraan Masyarakat Pra Sejahtera Di Kecamatan Weliman Kabupaten Malaka - Nahak, Juandry C.; Seran, Marisa S. B.; Mael, Medan Y (Universitas Medan Area, 2025)
This study aims to analyze the effectiveness of the Prosperous Rice Program (Rastra) in improving the welfare of the underprivileged community in Weliman District, as well as identify obstacles and recommendations to increase the effectiveness of the Rastra Program in Weliman District. This study uses qualitative methods with interviews, observations, and policy analysis to assess the effectiveness of the Rastra program in Weliman District. The results of the study show that the Rastra Program in Weliman District is not on target. This is due to the lack of deliberation in determining beneficiaries, so that the distribution tends to favor the family or acquaintances of local officials. In terms of quantity, this program has met the Rastra guidelines, where each recipient gets 15 kg of rice per month. However, the timeliness of distribution is still an obstacle, with delays ranging from 3 to 6 months, far from the provisions that should be done every month. Meanwhile, the quality of the rice provided is in accordance with the standards of suitability for consumption based on the Rastra guidelines. The effectiveness of this program can be increased by transparent recipient verification and improved distribution to be on time according to Rastra guidelines.